Analysis of marketing strategies in the context of revitalizing the tourist destination of Senggigi West Lombok - Permadi Lalu Adi; Tara Nur Aida Arifah; Septiani Emilia (SHS Web of Conferences, 2024)
The purpose of this study is to analyze and identify marketing strategies for the revitalization of West Lombok’s Senggigi Tourism Destination. The research method used in this study is a mixed method between qualitative and quantitative. The strategy analysis pattern used in analyzing marketing strategies in the Framework for Revitalization of Senggigi Tourism Destinations is SWOT analysis. The findings of this research show that the main strengths for marketing Senggigi tourism are that “Accommodation and supporting facilities are readily available in Senggigi” and “The Senggigi tourism destination has several attractions, including beaches, hills, and forests.” The main weaknesses were “ Tourism management has not been optimal for all tourism objects in Senggigi” and “accessibility on public transportation is not adequate for tourists.” Based on the SWOT Matrix, there were alternative marketing strategies that could be implemented, such as “improving and making attractive promotions for tourists; managing and maintaining well the tourism object area as the destination main product, and adding interesting annual events as a valuable addition to the product.”